CRISPR/Cas9 Targeted Editing of Genes Associated With Fungal Susceptibility in Vitis vinifera L. cv. Thompson Seedless Using Geminivirus-Derived Replicons - Olivares, Felipe; Loyola, Rodrigo; Olmedo, Blanca; Miccono, María de los Ángeles; Aguirre, Carlos; Vergara, Ricardo; Riquelme, Danae; Madrid, Gabriela; Plantat, Philippe; Mora, Roxana; Espinoza, Daniel; Prieto, Humberto (Frontiers in Plant Science, 2021)
The woody nature of grapevine (Vitis vinifera L.) has hindered the development of efficient gene editing strategies to improve this species. The lack of highly efficient gene transfer techniques, which, furthermore, are applied in multicellular explants such as somatic embryos, are additional technical handicaps to gene editing in the vine. The inclusion of geminivirus-based replicons in regular T-DNA vectors can enhance the expression of clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) elements, thus enabling the use of these multicellular explants as starting materials. In this study, we used Bean yellow dwarf virus (BeYDV)-derived replicon vectors to express the key components of CRISPR/Cas9 system in vivo and evaluate their editing capability in individuals derived from Agrobacterium-mediated gene transfer experiments of ‘Thompson Seedless’ somatic embryos. Preliminary assays using a BeYDV-derived vector for green fluorescent protein reporter gene expression demonstrated marker visualization in embryos for up to 33 days post-infiltration. A universal BeYDV-based vector (pGMV-U) was assembled to produce all CRISPR/Cas9 components with up to four independent guide RNA (gRNA) expression cassettes. With a focus on fungal tolerance, we used gRNA pairs to address considerably large deletions of putative grape susceptibility genes, including AUXIN INDUCED IN ROOT CULTURE 12 (VviAIR12), SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTER 4 (VviSWEET4), LESION INITIATION 2 (VviLIN2), and DIMERIZATION PARTNER-E2F-LIKE 1 (VviDEL1). The editing functionality of gRNA pairs in pGMV-U was evaluated by grapevine leaf agroinfiltration assays, thus enabling longer-term embryo transformations. These experiments allowed for the establishment of greenhouse individuals exhibiting a double-cut edited status for all targeted genes under different allele-editing conditions. After approximately 18 months, the edited grapevine plants were preliminary evaluated regarding its resistance to Erysiphe necator and Botrytis cinerea. Assays have shown that a transgene-free VviDEL1 double-cut edited line exhibits over 90% reduction in symptoms triggered by powdery mildew infection. These results point to the use of geminivirus-based replicons for gene editing in grapevine and other relevant fruit species.